P97 VALIDATION OF THE ACADEMIC RESEARCH CONSORTIUM HIGH BLEEDING RISK CRITERIA IN PATIENTS UNDERGOING PERCUTANEOUS CORONARY INTERVENTION: A SYSTEMATIC REVIEW AND METANALYSIS OF 10 STUDIES AND 67, 862 PATIENTS. (18th May 2022) - Esposito, L; Baldi, C; Silverio, A; Di Maio, M; Cancro, F; Buccheri, S; De Luca, G; Sarno, G; Bellino, M; Verdoia, M; Vecchione, C; Galasso, G
Abstract: Background: The Academic Research Consortium for High Bleeding Risk (ARC–HBR) has recently proposed, by consensus, twenty clinical criteria for the assessment of the bleeding risk after percutaneous coronary intervention (PCI). A major criterion was defined as any individual clinical condition conferring in isolation a risk for major bleeding ≥4% up to 1 year after PCI; instead, a minor criterion was considered to confer a bleeding risk of < 4%. The aim of this meta–analysis was to assess the performance of the ARC–HBR criteria in stratifying the risk of bleeding and ischemic events after PCI. Methods: MEDLINE, COCHRANE, Web of Sciences, and SCOPUS were searched for studies aimed at validating the ARC–HBR criteria in patients treated with PCI. The primary outcome measure of this meta–analysis was major bleeding. Results: The analysis included 10 studies encompassing 67, 862 patients undergoing PCI; the HBR definition was fulfilled in 44.7% of the cases. The risk of major bleeding was significantly higher in HBR vs. Non–HBR group (RR, 2.56, 95% CI 2.28–2.89). The average C–statistic was 0.64 (95% CI 0.60–0.68), indicating modest discrimination. The risk of intracranial hemorrhage, gastrointestinal bleeding, fatal bleeding, ischaemic stroke, cardiac death and all–cause death was higher in HBR vs. Non–HBR group. Despite a higher incidence of myocardial infarction and stent thrombosis in patients deemed at HBR, the rate of target lesion revascularization was comparable between groups (RR, 1.01, 95% CI 0.88–1.16). When assessed in isolation, the mean cumulative incidence of major bleeding at 1 year exceeded the cut–off value of 4% for all the major criteria and for two out of six minor criteria, including age ≥75 years and moderate chronic kidney disease (CKD) (Figure). Conclusion: The ARC–HBR definition identifies patients at higher risk of major bleeding and other adverse cardiovascular events after PCI. Almost all major criteria, but also two of the minor criteria, were individually associated with rates of major bleeding above 4% thus fulfilling the definition of major HBR criteria. These findings corroborate the ability of ARC–HBR major criteria in identifying PCI patients who are more likely to develop adverse events, but also suggest caution in the decision making of patients with isolated minor criteria, including age≥75 years and moderate CKD.